Labor supply with social interactions: econometric estimates and their tax policy implications - Andrew Grodner; Thomas J. Kniesner (Institute for the Study of Labor (IZA), 2007)
Our econometric research allows for a possible response of a person's hours worked to hours typically worked by members of a multidimensional labor market reference group that considers demographics and geographic location. Instrumental variables estimates of the canonical labor supply model expanded to permit social interactions pass a battery of specification checks and indicate positive and economically important spillovers for adult men. Ignoring or incorrectly considering social interactions in male labor supply can mis-estimate the response to tax reform by as much as 60 percent.
Keywords: 330; Labor supply; social interactions; reference group; instrumental variables; social multiplier; PSID; Arbeitsangebot; Arbeitszeit; Soziale Beziehungen; Modell-Spezifikation; Steuerreform; Steuerwirkung; USA